Bioactive growth hormone in humans: Controversies, complexities and concepts. (February 2020) - Hymer, Wesley C.; Kennett, Mary J.; Maji, Samir K.; Gosselink, Kristin L.; McCall, Gary E.; Grindeland, Richard E.; Post, Emily M.; Kraemer, William J.
Abstract: Objective: To revisit a finding, first described in 1978, which documented existence of a pituitary growth factor that escaped detection by immunoassay, but which was active in the established rat tibia GH bioassay. Methods: We present a narrative review of the evolution of growth hormone complexity, and its bio-detectability, from a historical perspective. Results: In humans under the age of 60, physical training (i.e. aerobic endurance and resistance training) are stressors which preferentially stimulate release of bioactive GH (bGH) into the blood. Neuroanatomical studies indicate a) that nerve fibers directly innervate the human anterior pituitary and b) that hind limb muscle afferents, in both humans and rats, also modulate plasma bGH. In the pituitary gland itself, molecular variants of GH, somatotroph heterogeneity and cell plasticity all appear to play a role in regulation of this growth factor. Conclusion: This review considers more recent findings on this often forgotten/neglected subject. Comparison testing of a) human plasma samples, b) sub-populations of separated rat pituitary somatotrophs or c) purified human pituitary peptides by GH bioassay vs immunoassay consistently yield conflicting results. Highlights: Growth hormone bioassays vs immunoassays differ and thus interpretation of acute responses and chronic adaptations differ Growth hormone release in response to external demands is variable and dependent upon the assay signal used for detection Growth hormone cells are heterogeneous and their biosynthetic pathways are different Growth hormone storage forms are functional amyloids